Микола Павлович Дашкевич: визнаний і незнаний діяч української науки - Марченко, Н.П. (Українська біографістика, 2010)
The issue researches the life of a philologist, historian, folklore specialist and bibliographer, pedagogue, secretary and head of St. Nestor Historical Society — Mykola Pavlovych Dashkevych (1852–1908), Ukrainian, who has long been seen as mostly Russian personality. It also analyses his activity as one of the founders of Roman Germanic studios in Ukraine, as a professor of St. Volodymyr University, important philologist and historian.